Aprendizajes y desafíos en la elaboración de documentos para la política pública en la Universidad de Chile - Pablo Riveros Argel; Pía Torres González; Jaqueline Meriño Vergara (INTER DISCIPLINA, 2026)
This article systematizes the Public Policy Documents (DPP, by its Spanish acro- nym) strategy developed by the University of Chile as an experience that articulates the science-policy interface. Methodologically, the article lies at the intersection between reflexivity and the systematization of experiences, describing three DPP formats: policy papers, position papers, and policy briefs. Based on their implementation, lessons learned are identified that cut across these formats. We propose plurality as an ethic of scientific advice, which assumes the diversity of knowledge and time as a constitutive part of the process. This entails accepting the possibility of not reaching definitive consensus and moving toward plausible formulations that recognize the complexity of the problems. The science-policy interface also requires the active incorporation of civil society as a legitimate interlocutor. The article problematizes the question of who participates in the coproduction of knowledge, opening up a critical reflection on the processes, ethical implications, and how to think about these approaches from a public university.